GENETIC VARIATION, HERITABILITY AND CORRELATION BETWEEN RESIN PRODUCTION CHARACTER OF Pinus merkusii HIGH RESIN YIELDER (HRY) IN CIJAMBU SEEDLING SEED ORCHARD (SSO) - Arida Susilowati Iswanto; Supriyanto Supriyanto; Iskandar Z. Siregar; Imam Wahyudi; Corryanti Corryanti (BIOTROPIA, 2013)
Selection high resin candidate P.merkusii is a series of breeding activities to get high resin production trait of pine trees.  In selection process of candidate tress, genetic diversity plays  very important role because higher genetic diversity will give higher opportunity to get source of genes for improved trait. Selection activities of high resin yielder candidates were started  in 2006 through a series of survey activity and morphological identification of candidate trees with high resin production. Specific information about traits genetically related to resin production in Cijambu Seedling Seed Orchard is still not determined yet , although based on resin distribution trend this SSO has the highest mean of resin production.  In this study, progenies planted in 1978 -1983 were evaluated to determine the effectiveness of previous selection, as well as the value of heritability and phenotypic traits that allegedly related with resin production. The results showed high value of coefficient genetic variation (CVG:16.08%), narrow sense heritability values for resin production trait (0.65) and resemble with previous research. This indicates that genetic factor was  dominant for resin production and selection activities has been done for 30 years was effective to get high yielder superior candidate.  Bark thickness, crown length and stem diameter trait was positively significant correlated to resin production, whereas level of pests and diseases was negatively significant correlated to resin production, it is possible that  the trait related with lighting conditions that supporting photosynthesis process and number of resin duct in the wood.  Key words: Selection, high resin yielder, P. merkusii, variation, heritability,phenotypic